ANALISA SISTEM RODA GIGI DIFERENSIAL PENGGERAK RODA BELAKANG KENDARAAN MOBIL LISTRIK (IKSA) - Pambudi, Tri Agung; Pramono, Gatot Eka; Yuliaji, Dwi (UNIVERSITAS IBN KHALDUN BOGOR, 2019)
Differential gears are one of the round transmission systems on cars, where the electric motor is the main activator of the electric car that has been integrated with the differential gear so the rotation of the electric motor is directly transmitted to the rear activator differential gear. In this study, an electric motor uses a 2200 W DC 60 v brushless motor, BLDC, motor, BM1424HQF-14A motor type. The maximum torque in the final gear is 600 Nm. This study focused on calculating the ratio of differential gears, tangential forces that occur on gears, calculation of gear torque. From the results and discussion on the calculation of the maximum torque in the final gear of 600 Nm, the maximum torque results in the pinion gear are obtained. When the pinion gear speed is at 1 rpm, the torque force generated is as large as it can be stated that the gears are safe to use with a motor power of 2.2 kW.